Mobility strategies in Latin American operational landscapes as a risk factor in times of covid-19 - Boccolini, Sara María (Universidad Pedagógica y Tecnológica de Colombia, 2022)
We built an explanatory hypothesis for an especially intense and early covid-19 diffusion pattern detected in Latin American regions where extractive activities of commodities for consumption in global markets predominate —even in comparison with nearby metropolitan regions—. To this end, we propose to consider them as fundamental operational landscapes in global urbanization processes; accordingly, the analysis in terms of mobility strategies found in these territories made it possible to identify specific factors determining the high rates of infection and circulation of the virus. To ensure the reliability and availability of data and to deepen the analysis and discussion of results, the agricultural production region of Córdoba (Argentina) was chosen as a case study. We processed socioeconomic and production statistics and rebuilt the dissemination of covid-19 with data disaggregated by locality between March 2020 and January 2021. The contrast of this information allowed us to affirm that the daily patterns of its inhabitants are the product of the unresolved dichotomy between logics derived from a historical development as rural communities and new logics determined by their articulation in global networks with high mobility of goods and people; this tends to amplify risk factors, even in comparison with metropolitan regions considered to have a higher health risk. In this way, the restructuring of these territories as an operational landscape could explain the pattern of spread of the virus and indicate its development trends in the medium term, becoming a strategic contribution to containment and sanitary remediation interventions and regional development policies.